Análise mutacional do feijão-de-corda (Vigna unguiculata) e do amendoim (Arachis hypogaea) para algumas características agronômicas - Sá, Maria Eugênia Lisei de (1984)
The mutational analysis of the peanut variety Tatu (Valencia) a tetraploid and the cowpea variety CE-315 a diploid, employing Nitrosometiyl urea (NMU) at a concentration of 0.02% was carried out in the experimental fields of Federal University of Ceara, in Fortaleza and Pentecoste. [...]